Development of Islamic Pawn-Broking services : differentiating profile of their respectice patrons - Shaari A. Hamid; Azlina Abdul Aziz (2003)
This paper seek to develop a comparative demographic and lifestyle profiles of the small independent islamicised conventional pawnshops vis-a-vis their larger institutionalised counterparts.